1969
DOI: 10.1002/ardp.19693020504
|View full text |Cite
|
Sign up to set email alerts
|

Die Gelstruktur der wasserhaltigen emulgierenden Salbe

Abstract: Die waseerhaltige emulgierende Salbe (etwa 70% H,O) des 3. Nachtrages zum DAB 6 bzw. des DAB 7 und ihre Ausgangsbeatandteile wurden elektronenmikroskopisch untersucht. Mittels einer neuen modifizierten Gefrieriitzungsmethode konnte das hypothetische Gelgeriist der plastischen wasserhaltigen emulgierenden Salbe elektronenmikroskopisch nachgewieaen und durch Stereoaufnahmen in seinem dreidimensionalen Feinbau analysiert werden. Gel-structure of the Hydrous Emulsifying OintmentThe hydrous emulsifying ointment (ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The fine structure of the gel was not observed because of the limits of resolution of the optical microscope. Electron micrographs of an anionic ternary system indicated that the gel was composed of straight chains of submicroscopical spherical particles interlinked to form a three dimensional network (Gstirner et al, 1969).…”
Section: B Formation Of Ternary System Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The fine structure of the gel was not observed because of the limits of resolution of the optical microscope. Electron micrographs of an anionic ternary system indicated that the gel was composed of straight chains of submicroscopical spherical particles interlinked to form a three dimensional network (Gstirner et al, 1969).…”
Section: B Formation Of Ternary System Networkmentioning
confidence: 99%
“…Photomicrographs of the gel and deformed globules were published for emulsions stabilised by the mixed emulsifiers sodium dodecyl sulphate/cetyl alcohol and cetrimide/cetostearyI alcohol by Barry (1968) and Barry and Saunders (1 970a). Gstirner et al (1969) provided electron micrographs of an anionic emulsion which showed a three dimensional gel network in the continuous phase.…”
Section: Emulsions Stabilised By Surfactant / Fatty Alcohol Mixed Emumentioning
confidence: 99%
“…The fine structure of the particulate region could not be seen clearly with the modulation contrast objectives presently available. Thus, we cannot say whether the particles are arranged in chains as reported by Gstirner et al (9) based on electron microscopy studies in a related system.…”
Section: Discussionmentioning
confidence: 76%
“…Of particular interest here is the suggestion made in these papers that particles of a surfactant-rich phase can sometimes form a network structure which imparts viscoelastic properties to even quite dilute formulations of this type, i.e., those containing over 90% water. Indeed, Gstirner et al (9) observed with electron microscopy a network consisting of interlocked chains of submicroscopic particles (0.1-1~m diameter} in a closely related system containing a mixture of longchain anionic surfactants and long-chain fatty alcohols. The particles appeared to be of more or less spherical shape.…”
mentioning
confidence: 99%
“…The interactions between hexachlorophene, polysorbate 20(Tween 20), and polyethylene glycol The properties and usual components of transparent gels were carefully reviewed by Hynniman and Lamy (481). A special technique to observe the structural features of such gels utilizing the electron microscope following a freezing step to prevent changes in micelles was reported (482). Such techniques are necessary, since the components of such gels and emulsions are very difficult to observe microscopically.…”
mentioning
confidence: 99%